Performance Evaluation of MANET Routing Protocols: Simulations and Experiments - Ikeda, Makoto; Barolli, Leonard; Hiyama, Masahiro; Kulla, Elis; Takizawa, Makoto (Computing and Informatics, 2012)
A Mobile Ad hoc Network (MANET) is a collection of wireless mobile terminals that are able to dynamically form a temporary network without any aid from fixed infrastructure or centralized administration. In this paper, we present the implementation and analysis of our implemented MANET testbed and simulation system considering Ad-hoc On demand Distance Vector (AODV) and Optimized Link State Routing (OLSR) protocols for wireless multi-hop networking. We investigate the effect of mobility and topology changing in MANET. We evaluate and compare the performance by simulation (using ns-2 simulator) and experiments in a real environment. In this work, we consider two models: stationary and mobile. We assess the performance of our testbed and simulation in terms of throughput, number of received packets and hop distance. From the results, we found that the AODV protocol has a good performance when the relay node is moving. Also, the AODV protocol provides a flexible and effective routing for indoor environments.